GaN channel waveguide with vertically polarity inversion formed by surface activated bonding for wavelength conversion. (1st May 2022) - Yokoyama, Naoki; Tanabe, Ryo; Yasuda, Yuma; Honda, Hiroto; Ichikawa, Shuhei; Fujiwara, Yasufumi; Hikosaka, Toshiki; Uemukai, Masahiro; Tanikawa, Tomoyuki; Katayama, Ryuji
Abstract: We proposed a nitride semiconductor transverse quasi-phase-matched wavelength conversion device with a polarity inverted structure along the vertical direction formed by surface-activated bonding and etching processes. Inductively coupled plasma etching of a GaN layer with maintaining a root mean square roughness of less than 2 nm in a 100 μ m square area was achieved even after deep etching of 1 μ m using Cl2 /Ar mixture gas and optimizing the antenna and bias powers. This smooth etching enabled surface-activated bonding of the ultrathin GaN layer with designed thickness. The fabrication process of the GaN polarity inverted channel waveguide was established.